1999
DOI: 10.1007/s005860050176
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic L5-S1 spondylolisthesis: report of three cases and a review of the literature

Abstract: IntroductionTraumatic lumbosacral spondylolisthesis is a very uncommon lesion. The literature testifies to this rareness, reporting only 22 cases over the last 50 years [1, 2, 4, 5, 7, 9-11, 13-15, 21, 22]. These include seven cases of pure bilateral dislocation [1,4,5,7,11,15,22]. The specific features of the lesion, as well as the different possible radiographic and clinical findings that characterize it, have encouraged many researchers to attempt to propose possible interpretations of the kinematics of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 20 publications
0
30
0
4
Order By: Relevance
“…With the fulcrum anterior to the spine, the resultant momentum, along with shear and tensile forces, results in a transverse disruption of the intervertebral mobile segment, from the supraspinous ligament to the anterior annulus [19]. To our knowledge, most of the reported traumatic lumbar dislocations have been at the L5-S1 level [3,4,7,8,9,10,11,14,16,22], and none have been a traumatic L4-5 dislocation. A previous study revealed the lumbar facet orientation in a normal lumbar spine, and noted that the facet joint and laminae are more sagittally oriented at the L4-5 level, while at L5-S1 they are more frontally oriented [21].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…With the fulcrum anterior to the spine, the resultant momentum, along with shear and tensile forces, results in a transverse disruption of the intervertebral mobile segment, from the supraspinous ligament to the anterior annulus [19]. To our knowledge, most of the reported traumatic lumbar dislocations have been at the L5-S1 level [3,4,7,8,9,10,11,14,16,22], and none have been a traumatic L4-5 dislocation. A previous study revealed the lumbar facet orientation in a normal lumbar spine, and noted that the facet joint and laminae are more sagittally oriented at the L4-5 level, while at L5-S1 they are more frontally oriented [21].…”
Section: Discussionmentioning
confidence: 84%
“…However, some seatbelt-associated injuries have been reported [2,5], among which bilateral lumbar facet dislocations are uncommon. Previous reports have noted only a few traumatic bilateral lumbar facet dislocations, all of which occurred at the lumbosacral junction [3,4,8,11], and some classifications of lumbar and lumbosacral injuries have been reported [1,6,13]. According to the main mechanism of injury and pathomorphological pattern, and in consideration of the prognostic aspects regarding healing potential, Magerl et al [13] comprehensively classified thoracic and lumbar injuries into three types.…”
mentioning
confidence: 99%
“…The forces producing the lesion have been postulated to be hyperflextion for the pure dislocations and hyperflexion in combination with compression or axial translation in cases with significant fractures of the fifth lumbar vertebrae. It is frequently associated with neurologic deficit, although total cauda equina lesion is rarely found 1, 4,5,10,11) . The current premise in the management of traumatic fracture dislocation of the lumbosacral junction is to restore the normal alignment and stabilize these highly unstable injuries, by open reduction of the dislocation and rigid fixation of the affected segment 3,12) .…”
Section: Discussionmentioning
confidence: 99%
“…Acute traumatic spondylolisthesis is a rare condition 3,4) . It usually involves subluxation or fracture-dislocation of the facet joints, which may be unilateral or bilateral.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic spondylolisthesis has consistently been linked to high-energy trauma despite the lack of agreement in the literature on the mechanism (i.e., forced hyper-extension, forced hyper-flexion with compression, or horizontal shear combined with rotation) [2][3][4][5]. Although a rare injury, a high index of suspicion and early investigation remains a cornerstone in the diagnosis.…”
mentioning
confidence: 99%